2017
DOI: 10.1111/ajco.12702
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and palliative care outcomes for patients of poor performance status treated with antiprogrammed death‐1 monoclonal antibodies for advanced melanoma

Abstract: Patients with poor baseline PS have a significantly lower OS and reduced response to anti-PD1. Further quality of life and palliative care research is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…Using multiple logistic regression to merge our Response Classifier output with known clinical predictors was crucial to generate a model with enhanced accuracy. In prior studies, ECOG performance status predicted survival and response to immunotherapy in patients with melanoma (30,31). We too found that the incorporation of performance status augmented prediction accuracy, likely because it accounts for critical patient information not necessarily reflected in tissue histology.…”
Section: Discussionmentioning
confidence: 55%
“…Using multiple logistic regression to merge our Response Classifier output with known clinical predictors was crucial to generate a model with enhanced accuracy. In prior studies, ECOG performance status predicted survival and response to immunotherapy in patients with melanoma (30,31). We too found that the incorporation of performance status augmented prediction accuracy, likely because it accounts for critical patient information not necessarily reflected in tissue histology.…”
Section: Discussionmentioning
confidence: 55%
“…The ECOG 2–3 group were also more likely to die in an acute hospital setting (62% vs. 23%. respectively; RR 2.68, 95% CI 1.17–6.51; p = 0.016) [48]. All hospitalisation within the last month of life was for the management of disease progression.…”
Section: Immune-related Adverse Events In Older Patientsmentioning
confidence: 99%
“…However, immunotherapies with their novel mechanisms of action can result in immune‐mediated side effects including rash, endocrinopathies, and, less frequently, severe toxicities involving pneumonitis, hepatitis, colitis, and myocarditis . Significant challenges have arisen in the clinic for health care providers to balance hope with realistic expectations as patients are counselled on these new treatments .…”
Section: Introductionmentioning
confidence: 99%